2022
DOI: 10.1093/hr/uhac238
|View full text |Cite
|
Sign up to set email alerts
|

The SmMYB36-SmERF6/SmERF115 module regulates the biosynthesis of tanshinones and phenolic acids in salvia miltiorrhiza hairy roots

Abstract: Tanshinone and phenolic acids are the most important active substances of Salvia miltiorrhiza, and the insight into their transcriptional regulatory mechanisms is an essential process to increase their content in vivo. SmMYB36 has been found to have important regulatory functions in the synthesis of tanshinone and phenolic acid, paradoxically, its mechanism of action in S. miltiorrhiza is not clear. Here, we demonstrated that SmMYB36 functions as a promoter of tanshinones accumulation and a suppressor of pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 60 publications
(69 reference statements)
0
8
0
Order By: Relevance
“…Transcription factors have the ability to regulate diverse processes, such as secondary metabolism, by interacting with DNA motifs in the promoter area of genes of interest [ 37 , 55 ]. This regulation is mediated by TFs interaction with itself or with other proteins, depending on its self-transcriptional activity; this activity is analyzed by yeast one-hybrid assays [ 55 ]. In this study, pGBKT7-RpMYB81 and pGBKT7-RpMYB98 were transformed into AH109 to verify whether there was self-activation.…”
Section: Discussionmentioning
confidence: 99%
“…Transcription factors have the ability to regulate diverse processes, such as secondary metabolism, by interacting with DNA motifs in the promoter area of genes of interest [ 37 , 55 ]. This regulation is mediated by TFs interaction with itself or with other proteins, depending on its self-transcriptional activity; this activity is analyzed by yeast one-hybrid assays [ 55 ]. In this study, pGBKT7-RpMYB81 and pGBKT7-RpMYB98 were transformed into AH109 to verify whether there was self-activation.…”
Section: Discussionmentioning
confidence: 99%
“…The phylogenetic tree showed that SmMYB36 was the closest gene to CbMYB32 . SmMYB36 has been demonstrated to interact with enzyme gene promoters or other transcription factors, directly or indirectly regulating the synthesis of tanshinones but inhibiting the synthesis of phenolic acids [ 26 , 27 ]. The phenomenon was discovered that a transcription factor interacting with several pathway genes was also found in other medicinal plants [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Plants harbouring knockout mutations of either gene had deeper red roots, with higher levels of lipid‐soluble compounds (Figure 1h,i). Overexpressing MYB36 in hairy roots promotes tanshinone accumulation while decreasing phenolic acid levels (Li et al ., 2022). However, MYB36 is primarily expressed in flowers and is homologous to some Arabidopsis MYB genes (Li and Lu, 2014).…”
Section: Figurementioning
confidence: 99%
“…Plants harbouring knockout mutations of either gene had deeper red roots, with higher levels of lipid-soluble compounds (Figure 1h,i). Overexpressing MYB36 in hairy roots promotes tanshinone accumulation while decreasing phenolic acid levels (Li et al, 2022). However, MYB36 is primarily expressed in flowers and is homologous to some Arabidopsis MYB genes (Li and Lu, 2014) More broadly, we demonstrated high-efficiency gene editing of both gene copies of various transcription factor genes regulating the biosynthesis of bioactive compounds in S. miltiorrhiza through a single transfection event using transgene-free CRISPR/Cas9 reagents in protoplasts, and regeneration of knockout plants through a newly established protoplast-toplant regeneration system.…”
mentioning
confidence: 99%